Pharmacokinetics of Recombinant Factor VIII (Recombinate) Using One-stage Clotting and Chromogenic Factor VIII Assay - Lee, C. A.; Owens, D.; Bray, G.; Giangrande, P.; Collins, P.; Hay, C.; Gomperts, E.; Schroth, P.; Barrowcliffe, T. (Thrombosis and Haemostasis, 1999)
In a study designed to demonstrate the safety and pharmacokinetics of a recombinant factor VIII (Recombinate) manufactured in Andover, MA and Thousand Oaks, CA, two different methods of factor VIII assay (one-stage clotting and Chromogenic substrate) were compared in vivo. The study was performed in four centres in the UK: London, Oxford, Cardiff and Manchester. Two pharmacokinetic studies, at least one week apart, were performed in 30 patients with severe haemophilia A (VIII:C < 2 IU/dl). A dose of 50 IU/kg was administered with sampling pre-infusion, and +0.25, 0.5, 1, 3, 6, 9, 12 and 24 h post-infusion. The aggregate 60 pharmacokinetic study showed a half-life of 12.7 and 13.0 h (p = 0.28) and recovery of 127 and 161 IU/dl (p = 0.0001) using one-stage clotting or chromogenic substrate respectively. In a supplementary experiment, 20 post-infusion samples were re-assayed by 1-stage and chromogenic assay using two plasma (20th British plasma standard and an “in-house” pooled normal plasma) and two concentrate standards, derived from the same type, but different batch of infused concentrate (Recombinate) and pre-diluted in either individual pre-infusion sample or in pooled commercial haemophilic plasma. The use of the Recombinate concentrate standard overcame the significant difference in FVIII levels between 1-stage and chromogenic assay methods when a plasma standard was used (p <0.0001). It is concluded that where potency dosing designation is carried out by an assay system different to that used in the clinical situation, the use of the recombinant concentrate as a standard in post-infusion plasma samples is likely to give more reliable and reproducible results.
Keywords: Recombinant FVIII (Recombinate); assay discrepancies